Analisis Kuat Tekan Beton dengan Penambahan Serat Plastik Daur Ulang sebagai Bahan Tambahan - Ahmad Firmansyah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The increasing concern about plastic waste has prompted researchers to explore sustainable alternatives in construction materials. This study investigates the compressive strength of concrete with the addition of recycled plastic fibers as supplementary material. The objective is to determine whether the integration of plastic fibers improves or compromises the mechanical performance of the concrete mix. Experimental methods involved creating concrete specimens with varying percentages (0%, 0.5%, 1%, and 1.5%) of shredded recycled plastic fibers. Standard tests for compressive strength were conducted after 28 days of curing. The results show that the addition of 0.5% and 1% plastic fibers enhances the compressive strength compared to the control mix, while the 1.5% composition results in a decrease. These findings suggest that there is an optimal range for plastic fiber addition that benefits concrete performance. The research contributes to sustainable construction practices by proposing an eco-friendly reuse of plastic waste.